The determinants of web-based corporate reporting by public listed companies in Malaysia / Saeid Homayoun - Homayoun, Saeid (2010)
The main objective of this thesis is to indicate the extent of Internet corporate disclosure among a sample of 100 top companies listed on the Bursa Malaysia by Market capitalization for the financial year ended 2007. This research made use of online search for the website survey and content analysis by physical observation of the websites. An Internet disclosure index of 61 content items including four major groups, namely; accounting and financial information, corporate governance, corporate social responsibility (CSR), contact details of investor relations and related conveniences, and 26 presentation format items including two major groups, namely; technological features, convenience and usability of website navigation support were used as a benchmark. The result indicates that the highest disclosures by the companies accrued for accounting and financial information attributes, while the lowest disclosures by companies accrued for technology features attributes. The result showed that more than 59 percent of Malaysian public listed companies published reasonably welldeveloped Internet-based reporting and achieved a quality score for ICR. On average, the frequency of the identified items disclosed by the companies for the content of the Web site was higher than for the presentation of information. Among the six categories, technological features theme was considered as a critical part that needed to be given more attention by the Malaysian firms. Therefore, there was a need for Malaysian companies to utilize more of the opportunities provided by the Internet technology in preparing the ICR. Most of the firms provided their full annual reports on the Internet in PDF format, while no companies use XBRL format. Agency and Signaling theories were used to generate hypotheses regarding the determinants of Internet corporate reporting. The results of Univariate analysis and multiple regressions indicated that among firm characteristics variables only profitability (proxy by return of equity), and among corporate governance mechanisms variables only board size (proxy by number of directors) are significantly associated with the extent of Internet corporate reporting. Evidence from this study recommendations were made to improve ICR by firms and to make the Internet a more reliable source for presentation of corporate reporting information. Further, presentation format and type of ICR affect investor judgments and suggests that regulations may be needed for the Internet reporting environment. The increasing use of ICR creates new challenges to management, regulators, and investors as there is no evidence guidance on this subject. The finding may also propose that new regulatory guidance in corporate governance lead to improved disclosure via ICR.